Lone Wolf Terrorism Trends in Indonesia - Avina Waliyanri; Muhamad Syauqillah (International Journal of Science and Society, 2022)
In the past few years, lone wolf terrorism has become a trending topic in the world of terrorism. We look at various definitions and trends of lone wolf terrorism from previous literature. This research aims to determine if there is a trend in lone wolf terrorism in Indonesia. The profile of the attacker is categorized based on the attacker’s age, gender, marriage status, occupation, and education, while the attack is categorized based on the attack’s target, region, choice of weapon, survival, casualties, and ideology or motive. The data is presented as descriptive statistics of qualitative nominal data in pie charts, and the results are discussed and analyzed. It was found that lone wolf terrorists do not have a single profile, but there are trends found where the attackers are typically male, single, in the 20s to 30s, self-employed, and at least graduated high school. The attacks usually target police, are based on ISIS ideology, uses either sharp weapon or explosives, and does not result in death. The attacker also typically survives, and all the attacks happened in the island of Java, Indonesia